-26+7p=2(7p-6)

Simple and best practice solution for -26+7p=2(7p-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26+7p=2(7p-6) equation:


Simplifying
-26 + 7p = 2(7p + -6)

Reorder the terms:
-26 + 7p = 2(-6 + 7p)
-26 + 7p = (-6 * 2 + 7p * 2)
-26 + 7p = (-12 + 14p)

Solving
-26 + 7p = -12 + 14p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-14p' to each side of the equation.
-26 + 7p + -14p = -12 + 14p + -14p

Combine like terms: 7p + -14p = -7p
-26 + -7p = -12 + 14p + -14p

Combine like terms: 14p + -14p = 0
-26 + -7p = -12 + 0
-26 + -7p = -12

Add '26' to each side of the equation.
-26 + 26 + -7p = -12 + 26

Combine like terms: -26 + 26 = 0
0 + -7p = -12 + 26
-7p = -12 + 26

Combine like terms: -12 + 26 = 14
-7p = 14

Divide each side by '-7'.
p = -2

Simplifying
p = -2

See similar equations:

| -8(8k-8)-3=-6k+3 | | (3x-1)(2x-5)=(3x-1)(x+2) | | 4n+27= | | 5n+18= | | 6=3*-9+21 | | 6(-2-6n)-4n=268 | | 2=4x-3+5x-8-6x-3 | | 147=-1-4(3+5m) | | (21x+2)= | | -2-6n=-4(1+2n) | | x+y=5y=3 | | 3+4t=4y+3 | | 9a-2a=8b-4b | | 25=3.75(6)+2.5 | | 36x^2=96x | | n-3/4=1(1/2) | | 2x-7=3x+0.25 | | l=50-1w | | 8(x-2)-5=4-3(x+1) | | -36+6v=4(6v+4)+2 | | -18.08-12.1g-11.48=-4.3g+18.8 | | 5x+20=36-x | | (x/2)=(6/5) | | 3w-16=-1+2-14w | | 2cos2x/2sin2x | | 24x^2-4x-54=6 | | 2(7x-2)=-116 | | 9n^2-76n+20=-12 | | 5x+3x-2x-5=4x-2 | | 10=2.5(2)+15 | | 16n^2+24n+9=0 | | 2/3*x=8/9 |

Equations solver categories